Fundamentals of Software Engineering - Ghezzi, Carlo; Jazayeri, Mehdi; Mandrioli, Dino. (Delhi : Prentice Hall, 2003)
Examines the latest trends and developments in the field of software engineering. The book illustrates various emerging frameworks of software testing and designs in traditional, structured and unstructured environments. Several worked-out examples and practice problems are included in each chapter
Keywords: Software Engineering; Inżynieria oprogramowania